“Se essa rua fosse minha...” Políticas Públicas para os loucos em situação de rua na capital amazonense - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
It was our perspective i) to conjecture about national policies aimed at street people in the Amazonian capital, specifically, ii) mapping the state and capital psychosocial care network, iii) discussing the change in the mental health care model, iv) presenting fictional narratives about the street crazy in the Amazonian capital, as subsidies for reflections, and v) establishing connections with other possibilities of care. The approach follows theoretical precepts such as that of Soriano (2004), in which the method results from the theory. Hence his close relationship with her. In this sense, the theory indicates the object of study that has certain characteristics and must be approached in a certain way. Thus, in the construction and analysis of data we intend to follow the sociohistorical method (KINOSHITA, 2016), in which the author presents reflective vision about the reality in health metal. We also discussed with Pagot (2012), who carried out a study on the subject in question and reflected on the discrimination given to the population segment, which starts from a whole political, economic and social context. Because we emphasize the attempt made to highlight some variables, such as: i) regional specificities, ii) obstacles to the applicability of the national policy, and iii) the need to expand the psychosocial care network. Our analysis considered historical specificities of phenomena, which were endowed with pertinent information to connect with the local reality. The task was based on fictional narratives that led to categories that we believe were relevant for formulation in the context of the results and discussions presented in this research.
Keywords: Pessoas em situação de rua; Políticas públicas; Saúde mental; Reforma psiquiátrica; CIÊNCIAS HUMANAS: PSICOLOGIA